Emerging threats of H5N1 clade 2.3.4.4b: cross-species transmission, pathogenesis, and pandemic risk - Azeem, Riaz-M; Yang, Ying-Shi; Sehrish, Siddique; Shi, Chun-Wei; Yang, Gui-Lian; Kumar, Suthar-Teerath; Yang, Wen-Tao; Wang, Chun-Feng (Frontiers in Cellular and Infection Microbiology, 2025)
H5N1 is a highly pathogenic avian influenza virus (HPAIV) with zoonotic potential, posing a significant risk to animal health, agriculture, and human public health. A particular strain, clade 2.3.4.4b, has spread globally and has been detected in various mammalian species—including cattle and a limited number of human cases—highlighting its potential to spark a pandemic. Investigating this specific clade represents a crucial step toward the development of effective preventive and therapeutic strategies. This mini-review aims to outline the etiology and pathophysiological mechanisms driving the current bird flu outbreak in cattle. A targeted literature search was conducted in PubMed for studies published between 2003 and 2025 using keywords such as “bird flu”, “cattle”, “mammals”, “H5N1”, and “pathogenesis”. This review explores the pathogenic mechanisms and clinical manifestations associated with HPAIV H5N1 infections in mammals specially in cattle. A key hypothesis is that the ongoing outbreak is fueled by molecular adaptations in the virus that enhance its ability to cross species barriers. As these mechanisms continue to be uncovered, there is a pressing need for high-quality research to inform pandemic preparedness, guide effective control strategies, and support the development of targeted vaccines and antiviral therapies.